2014
DOI: 10.1002/ps.3894
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and herbicidal activity of novel quinazoline-2,4-diones as 4-hydroxyphenylpyruvate dioxygenase inhibitors

Abstract: The present work indicated that the triketone-containing quinazoline-2,4-dione motif could be a potential lead structure for further development of novel herbicides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 36 publications
1
93
0
Order By: Relevance
“…(The crystal structures have been deposited at the Cambridge Crystallographic Data Centre and allocated the deposition numbers CCDC 1450978 and CCDC 1450980.) To synthesize the enol ester ( J ), the acid ( I ) is generally transformed into the corresponding acid chloride using SOCl 2 or ClCOCOCl . The limitation of this method is that it can only be utilized to prepare acid chlorides that are stable and not sensitive to SOCl 2 , ClCOCOCl or heat.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(The crystal structures have been deposited at the Cambridge Crystallographic Data Centre and allocated the deposition numbers CCDC 1450978 and CCDC 1450980.) To synthesize the enol ester ( J ), the acid ( I ) is generally transformed into the corresponding acid chloride using SOCl 2 or ClCOCOCl . The limitation of this method is that it can only be utilized to prepare acid chlorides that are stable and not sensitive to SOCl 2 , ClCOCOCl or heat.…”
Section: Resultsmentioning
confidence: 99%
“…Modification of the benzene ring of existing triketone HPPD herbicides has been an effective method of obtaining new HPPD inhibitors. Modified benzene rings of these novel HPPD herbicides include: benzo[ d ]oxazol‐2(3 H )‐one, 2,3‐dihydrobenzo[ b ]thiophene‐1,1‐dioxide, 4 H ‐thiochromene, quinoline, aryloxymethylene and quinazoline‐2,4(1 H ,3 H )‐dione …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, triketone HPPD herbicides with triketone and aromatic moieties are the most widely studied . For example, many studies have reported that the modification of the aromatic part of triketone derivatives is an effective way to obtain new inhibitors with improved potency. All the modified triketone derivatives mainly focused on aromatic component, which is replaced by heterocycles, aliphatic side chains, fused heterocycles and fused aromatics …”
Section: Introductionmentioning
confidence: 99%
“…Quinazoline is an important nitrogenous heterocyclic compound because of its antiviral, antibacterial and herbicidal activities . Previous studies have demonstrated quinazoline derivatives as potential medicinal drugs, and some of them have been used in clinical settings .…”
Section: Introductionmentioning
confidence: 99%